Effectiveness of an integrated agriculture, nutrition-specific, and nutrition-sensitive program on child growth in Western Kenya: a cluster-randomized controlled trial - Wegmüller, R; Musau, K; Vergari, L; Custer, E; Anyango, H; Donkor, WES; Kiprotich, M; Siegal, K; Petry, N; Wirth, JP; Lewycka, S; Woodruff, BA; et al. (Elsevier, 2022)
Background: Stunting rates remain unacceptably high in many regions, including sub-Saharan Africa. Agricultural programs have led to increased yields and household incomes but showed limited success in improving nutritional status.